The Scientific Pedagogical Need of Improving the Competence of Teachers of Physical Education and Sport Science - Toshtemirov Otabek Abidovich (Periodica Journal, 2023)
The article analyzes the current state of development of the communicative competence of future physical culture teachers, problems, shortcomings, and ways to overcome them. Also, the interpersonal, intergroup and collective, social forms of communication and their peculiarities in the professional pedagogical culture of future physical culture teachers
Keywords: education system; content of education; physical education